2020
DOI: 10.1021/acs.jpcc.0c03717
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Active Sites in the Dehydrogenation of Methanol on Pt/Al2O3 Catalysts

Abstract: Conversion of oxygenates derived from biomass is a promising strategy for the production of fuels and chemicals. The needed H 2 can be supplied simultaneously (and sustainably) via aqueous phase reforming (APR; C n H 2n O n + nH 2 O → nCO 2 + 2nH 2 ). APR is typically carried out over supported metal catalysts under liquid water. Dehydrogenation is the first constituent reaction in APR and involves both C−H and O−H bond cleavages; however, details about the mechanism and natures of the active sites remain unkn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 150 publications
0
16
0
Order By: Relevance
“…In our proposed mechanism (Scheme ), the alcohol substrate CPL undergoes dissociative adsorption on a Lewis acid–base pair on the support before an α-hydride undergoes reductive elimination onto an adjacent Pt species and leads to the formation of CPO . Given that the hydride transfer in such reactions is considered to be rate limiting, the morphology of the supported Pt species will undoubtedly have a significant impact on the rate of CPL conversion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our proposed mechanism (Scheme ), the alcohol substrate CPL undergoes dissociative adsorption on a Lewis acid–base pair on the support before an α-hydride undergoes reductive elimination onto an adjacent Pt species and leads to the formation of CPO . Given that the hydride transfer in such reactions is considered to be rate limiting, the morphology of the supported Pt species will undoubtedly have a significant impact on the rate of CPL conversion.…”
Section: Resultsmentioning
confidence: 99%
“…In our proposed mechanism (Scheme 2), the alcohol substrate CPL undergoes dissociative adsorption on a Lewis acid−base pair on the support before an α-hydride undergoes reductive elimination onto an adjacent Pt species and leads to the formation of CPO. 68 Given that the hydride transfer in such reactions is considered to be rate limiting, the morphology of the supported Pt species will undoubtedly have a significant impact on the rate of CPL conversion. From the testing data presented (Figures 1 and Tables 2 and S1), STEM analysis (Figures 2 and S2), in situ CO-DRIFTS experiments (Figures 4A and S3), and analogous modeling data (Figure 9), we can propose (with confidence) that the activity of the Pt species present in these materials is of the order 2D Pt > Pt nanoparticles > cationic Pt.…”
Section: Derivation Of the Surface Mechanismmentioning
confidence: 99%
“…At APR conditions the water gas shift reaction (WGS) equilibrium is almost completely displaced to products, yielding a gas product mainly composed by hydrogen and carbon dioxide [16][17][18]. In addition to reforming and WGS reactions, additional reactions occurring at APR conditions leading to the production of different water-soluble hydrocarbons via Fischer-Tropsch route, hydrogenation and dehydration [19,20]. APR process can be considered to involve two main routes, namely i) C-C, C-H and O-H bonds cleavage and WGS; and ii) C-O bonds rupture and alkane and formation of carbohydrates such as acids, sugar alcohols, etc.…”
Section: Introductionmentioning
confidence: 99%
“…APR process can be considered to involve two main routes, namely i) C-C, C-H and O-H bonds cleavage and WGS; and ii) C-O bonds rupture and alkane and formation of carbohydrates such as acids, sugar alcohols, etc. [19,21,22]. Regarding catalysts for APR, the most studied have been Group VIII to X metals due to higher activity in C-C bond cleavage [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…[2] Other works relate to the decomposition of methanol and formaldehyde to form hydrogen on Pt/Al2O3, Ru-Pt, Pt3/Ni(1 0 0), Zn/Cu(1 1 1), Pd/Zn(1 1 1), Pt13, Pt7, Pt3Cu4, Cu7, etc. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]32] The O-H cleavage or C-H cleavage occurs first depending on the catalytic material used. For instance, Desai and co-workers examined the adsorption of methanol over Pt(1 1 1) in vacuum and concluded that dehydrogenation pathways starting from the activation of the C-H bond are easier than these of the O-H bond.…”
Section: Introductionmentioning
confidence: 99%